Kulturowy kontekst zarządzania kadrami w przedsiębiorstwie polskim działającym w skali międzynarodowej - Kmiotek, Krystyna; Kopertyńska, Maria Wanda (Cultural context of human resource management in a Polish enterprise which is active on an international scale, 2006)
The aim of the article is to present some main problems connected with human resource management in conditions of activity abroad using the example of one enterprise. Some elements of labour management process are shaped by various factors. In the time of progressive globalization the most important among them are the cultural factors. On the basis of experience of Transsystem enterprise main problems connected with the realization of personal management were presented. The problems concerned Polish employees who worked abroad. The special attention was paid to the impact of cultural factors.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 364-371